Preadmission Application of 2% Chlorhexidine Gluconate (CHG): Enhancing Patient Compliance While Maximizing Skin Surface Concentrations. (28th December 2015) - Edmiston, Charles E.; Krepel, Candace J.; Spencer, Maureen P.; Ferraz, Alvaro A.; Seabrook, Gary R.; Lee, Cheong J.; Lewis, Brian D.; Brown, Kellie R.; Rossi, Peter J.; Malinowski, Michael J.; Edmiston, Sarah E.; Ferraz, Edmundo M.; et al.
Abstract : OBJECTIVE: Surgical site infections (SSIs) are responsible for significant morbidity and mortality. Preadmission skin antisepsis, while controversial, has gained acceptance as a strategy for reducing the risk of SSI. In this study, we analyze the benefit of an electronic alert system for enhancing compliance to preadmission application of 2% chlorhexidine gluconate (CHG). DESIGN, SETTING, AND PARTICIPANTS: Following informed consent, 100 healthy volunteers in an academic, tertiary care medical center were randomized to 5 chlorhexidine gluconate (CHG) skin application groups: 1, 2, 3, 4, or 5 consecutive applications. Participants were further randomized into 2 subgroups: with or without electronic alert. Skin surface concentrations of CHG (μg/mL) were analyzed using a colorimetric assay at 5 separate anatomic sites. INTERVENTION: Preadmission application of chlorhexidine gluconate, 2% RESULTS: Mean composite skin surface CHG concentrations in volunteer participants receiving EA following 1, 2, 3, 4, and 5 applications were 1, 040.5, 1, 334.4, 1, 278.2, 1, 643.9, and 1, 803.1 µg/mL, respectively, while composite skin surface concentrations in the no-EA group were 913.8, 1, 240.0, 1, 249.8, 1, 194.4, and 1, 364.2 µg/mL, respectively (ANOVA, P <.001). Composite ratios (CHG concentration/minimum inhibitory concentration required to inhibit the growth of 90% of organisms [MIC 90 ]) for 1, 2, 3, 4, or 5 applications using the 2% CHG cloth were 208.1, 266.8, 255.6, 328.8, and 360.6, respectively, representing CHG skin concentrations effective against staphylococcal surgical pathogens. The use of an electronic alert system resulted in significant increase in skin concentrations of CHG in the 4- and 5-application groups ( P <.04 and P <.007, respectively). CONCLUSION: The findings of this study suggest an evidence-based standardized process that includes use of an Internet-based electronic alert system to improve patient compliance while maximizing skin surface concentrations effective against MRSA and other staphylococcal surgical pathogens. Infect. Control Hosp. Epidemiol. 2016;37(3):254–259